Clinical spectrum of incomplete kawasaki disease in thailand - Rekwan Sittiwangkul (2018)
Background: Inadequate diagnostic criteria in incomplete Kawasaki disease (KD) patients may lead to misdiagnosis and delayed treatment. However, the risk of coronary artery aneurysm in these patients remains uncertain. Aim: To investigate differences in clinical, laboratory and echocardiographic variables between patients with incomplete KD and classic KD. Method: The medical records of 208 KD patients treated between January 2001 and December 2009 in the Department of Pediatrics, Chiang Mai University Hospital were reviewed retrospectively. Patients with three or fewer major criteria were defined as having incomplete KD. Results: Of the 208 KD patients, 61 (29%) had incomplete KD. In those with incomplete KD, a significantly higher proportion were male (73.8% vs 59.2%, P=0.03), the diagnosis was made later [mean (SD) day 9.0 (4.2) vs 7.2 (2.5), P=0.003], there was a higher rate of delayed diagnosis (>10 days, 21% vs 10%, P=0.02) and the presence of five major criteria was less common. The proportion of associated symptoms (irritability, upper respiratory tract symptoms, diarrhoea, vomiting and reactivation of BCG) and laboratory findings (pyuria, haemoglobin level, white blood count, polymorphonuclear cells, platelet count, erythrocyte sedimentation rate and serum albumin) were comparable in patients with incomplete KD and classic KD. The incomplete KD group tended to have a higher proportion of coronary artery abnormalities but the difference was not statistically significant (38% vs 25%, P=0.09). However, a significantly greater proportion of the group with incomplete KD had large aneurysms (10% vs 1%, P=0.009). Conclusions: Incomplete KD and classic KD have the same disease spectrum. Owing to the absence of some major criteria, incomplete KD can be more difficult to diagnose, which can result in delayed diagnosis and a greater risk of large coronary aneurysms. © W. S. Maney & Son Ltd 2013.